2020
DOI: 10.1021/acsomega.0c04362
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Electrogenic Gut Bacteria

Abstract: While electrogenic, or electricity-producing, Gram-negative bacteria predominantly found in anaerobic habitats have been intensively explored, the potential of Gram-positive microbial electrogenic capability residing in a similar anoxic environment has not been considered. Because Gram-positive bacteria contain a thick non-conductive cell wall, they were previously believed to be very weak exoelectrogens. However, with the recent discovery of electrogenicity by Gram-positive pathogens and elucidation of their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
32
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 35 publications
0
32
0
Order By: Relevance
“…The ec-MP presented here will allow a true parallelization of the microbial electrochemical screening and microbial electrochemically driven selection. This will open the door to perform microbial resource mining in habitats that are already well known for harbouring EAM like wastewater and soil ( Koch and Harnisch 2016a ; Logan et al, 2019 ) but also recently discovered ones like the oral ( Naradasu et al, 2020 ) or gut ( Tahernia et al, 2020b ; Rago et al, 2021 ) microbiome and especially to explore new habitats as resources. Further, we foresee that already exploited EAM, for instance, for microbial electrosynthesis of chemical building blocks ( Mayr et al, 2019 ; Wu et al, 2019 ), can be further improved using concepts and tools that are well established (for non-electrochemical means) like site directed mutagenesis, CRISPR-CAS, and techniques beyond in high-throughput ( Alves et al, 2017 ; Fan et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The ec-MP presented here will allow a true parallelization of the microbial electrochemical screening and microbial electrochemically driven selection. This will open the door to perform microbial resource mining in habitats that are already well known for harbouring EAM like wastewater and soil ( Koch and Harnisch 2016a ; Logan et al, 2019 ) but also recently discovered ones like the oral ( Naradasu et al, 2020 ) or gut ( Tahernia et al, 2020b ; Rago et al, 2021 ) microbiome and especially to explore new habitats as resources. Further, we foresee that already exploited EAM, for instance, for microbial electrosynthesis of chemical building blocks ( Mayr et al, 2019 ; Wu et al, 2019 ), can be further improved using concepts and tools that are well established (for non-electrochemical means) like site directed mutagenesis, CRISPR-CAS, and techniques beyond in high-throughput ( Alves et al, 2017 ; Fan et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…characterized microbial extracellular electron transfer capabilities and capacities of five gut bacteria: Staphylococcus aureus , Enterococcus faecalis , Streptococcus agalactiae , Lactobacillus reuteri , and Lactobacillus rhamnosus ( Figure a). [ 103 ] From the study, S. aureus, E. faecalis , and S. agalactiae exhibited distinct electrogenic capabilities, and their power generations were comparable to that of well‐known Gram‐negative exoelectrogen, S. oneidensis . This work demonstrated that many Gram‐positive gut bacteria can transfer electrons to the exterior of their cells and this finding has enormous upside potential for the fields of biosensing, biocomputing, and biosynthesis.…”
Section: Applications For Poweringmentioning
confidence: 99%
“…Electrogenic bacteria are a promising element for biosensing because they produce quantifiable electricity by sensing and responding to a wide variety of external signals including [103] Copyright 2020, American Chemical Society. b) A wearable microbial fuel cell using human skin bacteria.…”
Section: Applications For Sensingmentioning
confidence: 99%
See 1 more Smart Citation
“…[10,11] Wearable or implantable biobatteries have been proposed that use human skin or gut bacteria and feed off sweat or other organics available in the human body. [12,13] However, because these biobatteries use heterotrophs that feed and generate power from organic Bacteria-powered biobatteries using multiple microbial species under well-mixed conditions demonstrate a temporary performance enhancement through their cooperative interaction, where one species produces a resource that another species needs but cannot synthesize. Despite excitement about the artificial microbial consortium, those mixed populations cannot be robust to environmental changes and have difficulty generating long-lasting power because individual species compete with their neighbors for space and resources.…”
mentioning
confidence: 99%